Sea Levels Dynamical Downscaling and Climate Change Projections at the Uruguayan Coast - Jackson, Michelle; Fossati, Monica; Solari, Sebastian (Frontiers in Marine Science, 2022)
This work implements a dynamical downscaling approach, based on a set of nested bidimensional hydrodynamic models, to quantify the expected changes in the total sea level climate and its components for the Uruguayan coast, using surface wind and sea level pressure projections from global climate models generated during the Phase 5 of the Coupled Models Inter-Comparison Project, considering three time horizons: historical period (1986-2005), short term (2027-2045) and long term (2082-2100), and the future scenarios RCP 4.5 and RCP 8.5. It is concluded that the main contribution to the projected changes in the area is the regional mean sea level rise, followed in importance by the effect that the increase in the water depth has on the amplitude of the tidal components. Moreover, it is concluded that changes in the meteorological residuals (or surges), associated with potential changes in the atmospheric circulation patterns, are negligible in the study area. The obtained results reinforce the need to resort to dynamic downscaling for projecting total sea level changes in areas characterized by wide and shallow continental shelfs and estuaries, as this approach allows to resolve the interactions that may arise between tides, surges and the mean sea level rise, something that cannot addressed with an approach based solely on statistical downscaling.